Including pharmacists on consultant-led ward rounds: a prospective non-randomised controlled trial - Miller, Gavin (Clin Med (Lond), 2011)
This study aimed to compare interventions made by pharmacists attending consultant-led ward rounds in addition to providing a ward pharmacy service, with those made by pharmacists providing a ward pharmacy service alone. A prospective non-randomised controlled study on five inpatient medical wards was carried out at two teaching hospitals. A mean of 1.73 physician-accepted interventions were made per patient for the study group, compared to 0.89 for the control (Mann Whitney U, p<0.001) with no difference between groups in the nature or clinical importance of the interventions. One physician-accepted intervention was made every eight minutes during the consultant-led ward rounds, compared to one every 63 minutes during a ward pharmacist visit. Pharmacists attending consultant-led ward rounds in addition to undertaking a ward pharmacist visit make significantly more interventions per patient than those made by pharmacists undertaking a ward pharmacist visit alone, rectifying prescribing errors and optimising treatment.